Sickness and peripheral dizziness: A review - Sergei V. Lilenko (Consilium Medicum)
In this lecture, some aspects of vestibular pathology propedeutics are highlighted. The necessity of careful vestibulosensory reactions analysis by different physicians (ENT specialist, neurologist, internist, general practitioner) is emphasized. Main patients’ complaints (vertigo and unsteadiness) are distinguished between. Special attention is paid to the classification of these vestibulosensory reactions on their duration and periodicity. The terms (sickness itself and balance disorders that may be concomitant symptoms of kinetosis) are clearly defined. Theories and clinical manifestations of sickness syndromes and motion sickness are described in details. Clinical variants of peripheral and central vestibular dysfunction are analyzed. The importance of computerized technics of vestibulometry (electrooculography, video oculography and computer dynamic posturography) in order to make a topic diagnosis of vestibular dysfunction and to assess visual-vestibular interaction in sickness is emphasized.